Tożsamość upamiętniona w przestawieniach świętych. Przykład wczesnochrześcijańskich mozaik w rotundzie w Salonikach w Grecji - Matczak, Magdalena Domicela (Folia Praehistorica Posnaniensia, 2016)
The article aims at presenting the mosaics from the dome of the early Christian church – the Rotunda in Thessaloniki, Greece. The function of the mosaics are twofold: (a) the portrayal of the early Christian identity and (b) the construction of the identity of the spectators – the Christians. The mosaics depicted thirteen Saints and were composed of the elements originating from ancient art that were used to strengthen a new Christian identity. The Saints were depicted as orants wearing garments, which are traditionally reserved to the high officials. Their eyes, hair, and garments were depicted in purple that is the colour conventionally restricted to the emperor. In this way, the Christians emphasised the high social status given to the Saints and strengthened their identity. Furthermore, these modes of representation had a profound impact upon the spectators creating and maintaining their identity.